2017
DOI: 10.15421/021721
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of changing adaptation potential and morpho-biochemical parameters of erythrocytes in students with different modes of daily activity after physical loading

Abstract: The aim of this work was to identify morpho-functional and biochemical changes in erythrocytes in students with different daily educational -training regimens after dosed physical exertion. The study involved 50 male students aged 20–22 years who study at the Faculty of Physical Education and Sports. Of these, 25 were untrained students (control group) and 25 were students studying for the highest sports qualification who were engaged in sports in which training was conducted to improve overall endurance (skii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 26 publications
1
13
0
3
Order By: Relevance
“…Earlier works by Popel 'et al, [2,3] have shown that athletes after competitions have an accumulation of acidic metabolites in peripheral blood, especially lactate. In this case, the shift of the pH towards the acid reaction (up to 7.26) occurs due to the activation of the synthesis of 2,3-DFG.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Earlier works by Popel 'et al, [2,3] have shown that athletes after competitions have an accumulation of acidic metabolites in peripheral blood, especially lactate. In this case, the shift of the pH towards the acid reaction (up to 7.26) occurs due to the activation of the synthesis of 2,3-DFG.…”
Section: Discussionmentioning
confidence: 95%
“…In a number of studies [2,3,11] it was shown that when practicing strength sports, special requirements are made to the functional reserves of the athlete's cardio-respiratory system. This immediately affects the functional state of the peripheral circulation and is often associated with the level of erythrocyte hemostasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations